THE EFFECT OF USING DIFFERENT CONCENTRATIONS OF TERMITE SOIL SOLUTION ON ADHESION AND HATCHING OF AFRICAN CATFISH EGG - Siti Masfiroh; Sukendi Sukendi; Netti Aryani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTThis research was conducted in May-June 2021 at the Fish Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine, Riau University, Pekanbaru. The purpose of this study was to determine the effect of different concentrations of termite soil solution on egg adhesion, hatchability and survival rate of African catfish larvae. The method used is an experimental method with a Completely Randomized Design (CRD) model with 4 treatments and 3 replications. The concentration of termite soil used was P1= Immersion of African catfish eggs into termite soil solution with a concentration of0 gram(as a control). P2= Immersion of African catfish eggs into termite soil solution with a concentration of 2 gram/L water. P3= Immersion of African catfish eggs into termite soil solution with a concentration of 4 gram/L of water. P4= Immersion of African catfish eggs into termite soil solution with a concentration of 6 gram/L of water.. Eggs used1 gram/ treatment. Eggs were spread in an aquarium of 12 units with a capacity of40 Lfilled with 20L water/container. The results showed that different concentrations of termite soil solution had an effect on egg adhesion, fertilization rate, hatching rate, and larval survival. The best treatment was P3 (4 g/L) which produced 86.84% adhesion, 80.57% fertilization rate, 80.35% hatching rate, and 92.02% survival rate.Kata Kunci: African catfish, egg adhesion, termite soil.